Comparison of magnesium hydroxide/expanded Graphite composites for thermal energy storage in cogeneration nuclear power plants. (December 2017) - Zamengo, Massimiliano; Kato, Yukitaka
Abstract: Thermal energy storage via reversible chemical reactions is proposed for the assisting cogeneration in nuclear power plants (NPP) for district heating or middle-temperature industrial processes. Thermal energy at 350-400 ° C from NPP can be stored or released by operating reversible dehydration of magnesium hydroxide (Mg(OH)2 ) and the hydration of magnesium oxide (MgO). The packed beds can be transported to a different site for reutilization of heat. Expanded graphite (EG) was utilized as thermal conductivity enhancer for Mg(OH)2 and MgO. Composites of Mg(OH)2 and EG, named EM8 and EM4, were obtained by mixing Mg(OH)2 to EG with different mass mixing ratio [g of Mg(OH)2 : g of EG], respectively 8:1 and 4:1. EM8 and EM4 were compressed in figure of tablets (diameter of 10 mm, thickness 6 mm). Heat storage/output experiments were conducted on a packed bed reactor (diameter 48 mm, height 48 mm). Dehydration in a packed bed of EM4 tablets resulted faster than in a bed of EM8 ones, but a larger amount of thermal energy could be stored in the EM8 packed bed (in 60 min, 467 MJ mbed -3 for EM8 bed, 379 MJ mbed -3 for EM4 bed). The effect of thermal conductivity enhancement was investigated numerically. Finally, the volumes of packed beds of EM8 and EM4 tablets required for thermal energy storage from a nuclear power plant were estimated.